Bridging the Funding Gap: Issues Militating Against the Teaching of English Language in Junior Secondary Schools in Anambra State, Nigeria - Anueyiagu Oluchukwu Ann; Ogechukwu Mary Nwanna (PT. Pusmedia Group Indonesia, 2025)
Nigeria is still struggling to attain quality in its education due to poor funding to the sector. There are known factors suppressing the actualization of quality education in the country which includes; dilapidated facilities and lack of commitment of stakeholders in maintaining and innovating them, very poor funding and management as well as bad governance. Teaching and learning English language are also affected by these factors. This This study seeks to identify the problems militating against the teaching and learning of English language, it also analyzed the implications of these problems on the performance of junior secondary school students in English language in Awka South local government area of Anambra State. The research adopted a descriptive survey research design in addressing the research problem in the study location. A total of 250 respondents constitute the research population (comprising 200 junior secondary school students and 30 English language teachers purposively sampled from 10 junior secondary schools). Data were collected using a self-designed questionnaire. Descriptive statistics were used to analyze the data collected from the field. Results from the study findings reveal that too much work load, poor teacher’s welfare, inadequate facilities, lack of proficient teachers, poor school management, overcrowded classrooms are negatively associated with the effective teaching of English language in the study location. The research concluded that inadequate funding has significantly contributed to the poor teaching of English language in Awka South local government area of Anambra State. Based on the results from the study findings, this research recommends that government at all levels and stakeholders in private sector should employ more teachers, implement good teachers’ welfare program and funds, provide sufficient facilities and resources, encourage the use of English language by providing more scholarships, training and competitions programmes for both teachers and students. Also, there is need for English language teachers to be engaged in professional development, attending trainings, and deploy the best methods in teaching English language.